Applicability of a magnetic bucky gel for microextraction of mercury from complicated matrices followed by cold vapor atomic absorption spectroscopy. Issue 8 (23rd May 2020) - Jamshidi, Sara; Rofouei, Mohammad Kazem; Seidi, Shahram; Emmer, Åsa
ABSTRACT: A new eco-friendly bucky gel nano sorbent consisting of magnetic grapheneoxide (MGO) and an ionic liquid (IL) was used based on dispersive extraction technique followed by cold vapor atomic absorption spectroscopy for determination of mercury in river water, milk, omega-3 supplements, and lipstick. The optimum conditions for extraction were 50 mg of sorbent (mass ratio IL/MGO: 26), 8 min vortexing, acetate buffer pH = 4, and for desorption 3 min vortexing of HNO3 (1 mL). The limits of detection, quantification, preconcentration factor and extraction recovery were found at 0.57, 1.88 µg L −1, 21 and 84%. Relative standard deviation (RSD) was 6.5% ( n = 3).